Ionosphere over Ukrainian Antarctic Akademik Vernadsky station under minima of solar and magnetic activities, and daily insolation: case study for June 2019 - Bogomaz, O.V.; Shulha, M.O.; Kotov, D.V.; Zhivolup, T.G.; Koloskov, A.V.; Zalizovski, A.V.; Kashcheyev, S.B.; Reznychenko, A.I.; Hairston, M.R.; Truhlik, V. (Український антарктичний журнал, 2019)
We present ionospheric observational results obtained over Ukrainian Antarctic Akademik Vernadsky station. Ionospheric parameters (peak electron density and height, electron density and electron and ion temperatures in the topside) during the period near the local winter solstice in the Southern Hemisphere (June 28—29, 2019) are considered. The main objective is to show distinctive features of variations in ionospheric parameters during a prolonged period with very low solar and magnetic activities, and minimal daily insolation. У статті представлені результати спостережень іоносфери над Українською антарктичною станцією “Академік Вернадський”. Розглянуто параметри іоносфери (висота максимуму шару F2 та концентрація електронів на цій висоті, концентрація електронів, температури електронів та іонів у зовнішній іоносфері) впродовж періоду поблизу локального зимового сонцестояння у Південній півкулі (28–29 червня 2019 р.). Мета роботи. Показати відмінні риси варіацій параметрів іоносфери під час тривалого періоду з дуже низькою сонячною та магнітною активністю та мінімальною добовою інсоляцією.